A comparative description of the larvae of Psychomyia pusilla (Fabricius 1781), Metalype fragilis (Pictet 1834), and Paduniella vandeli Décamps 1965 (Trichoptera: Psychomyiidae) and comments on the larvae of other species belonging to these three genera - Tachet, Henri; Coppa, Gennaro; Forcellini, Maxence (Zootaxa, 2018)
The morphology of the larvae of three French species of Psychomyiinae: Psychomyia pusilla, Metalype fragilis and Paduniella vandeli are described. A set of characters on the head, the prothorax, and the anal prolegs makes it possible to identify the larvae of the fourth and fifth instars. A brief study of the world distribution of the genera Psychomyia, Metalype, and Paduniella is presented. An examination of the larvae of these three genera from literature data and personal observations offered us the possibility to test the validity of the set of characters obtained for the three French species. A key (with comments) of the three genera is provided.